Elective Percutaneous Coronary Interventions (PCI) in 100 Cases in a Centre Without On-site Cardiac Surgery Support - Badrul, Md Nurul Afsar; Ahmed, Kamal; Rahman, Sufia (Medicine Today, 2013)
Since its introduction in 1977, Percutaneous Coronary Interventions (PCI) is an important tool in the treatment of coronary artery disease (CAD). It is a retrospective analysis of data of 100 cases (132 vessels). The mean age was 50.9 years (range 30-70) with 90 (90%) male and 10 (10%) female. Indication of PCI includes acute and old MI, Chronic stable angina and unstable angina were 48 (48%), 33 (33%) and 19(19%) respectively. Procedure done in total 132 vessels among 100 patients. most of the cases were single vessels disease (SVD) {68 (68%} followed by double vessel disease (DVD) {30(30%)} , triple vessel disease (TVD) {02 (02%)} and chronic total occlusion (CTO) {02 (02%)}.Cobalt chromium was commonly used stent (117 (88.6%) followed by drug illuting stent (DES) 12 (9.1%) and bare metal stent (BMS) 3 (2.3%). Among the site of the stent insertion left anterior descending (LAD) 62 (47%), right coronary lesion (RCA) 37 (28), left circumplex artery (LCX) 33 (25%).Maximum stent length was 35 mm, minimum 10mm. Maximum stent diameter was 3.5 mm whereas minimum diameter 2.5 mm. The mean pretreatment reference diameter was 2.55 ± 0.20 mm and post treatment diameter 2.70 ± 0.45 mm. Angiographic, procedural and clinical success rate were 100%, 98% and 98% respectively. Major adverse cardiovascular event (MACE) {periprocedural MI} occurred in 2 (02 %) cases. Minor cardiovascular complications revealed vascular haematoma 2 (02%), bleeding from access site in 1 (01%), transient ventricular fibrillation (VF) in 3 (03%) cases. There was no hospital death, emergency CABG before discharge from hospital. Angiographic, procedural and clinical success rate were excellent with a little MACE and event free survival within 30 days follow up. So, PCI is a safe and effective method of myocardial revascularization irrespective of lesion morphology and type of stents used at immediate and 30 days follow up. DOI: http://dx.doi.org/10.3329/medtoday.v24i1.14106 Medicine TODAY Vol.24(1) 2012 pp.8-11